SUSTAINABILITY LEVEL OF DENSELY POPULATED AREA: JATIMULYO URBAN COMMUNITIES, LOWOKWARU DISTRICT, MALANG CITY - S Haryani (TATALOKA, 2019)
Large cities still peak the interests of some Indonesian society. Big city development as the center of economic activity is a powerful pull for society, influencing high workforce from both inside and outside of the city, causing a strong current of urbanization. One main problem that always accompanies urban areas development is density population. Urbanization has caused a very rapid explosion in the city population; one implication is the clumping workforce in large Indonesian cities. The high number of people who choose to settle in the city increase the number of both legal and illegal settlements. In the high-density settlement, many houses are not liveable and irregular. The densely populated settlements find many houses unfit for habitation and irregular. The research aims to formulate the sustainability level of Urban communities, Lowokwaru District, Malang City using quantitative method through sustainability level calculation. Jatimulyo Urban Communities is measured by the sustainability criteria of density, diversity, mixed-use, and compactness to formulate the related sustainable urban spatial structure. Interpretation of the calculation results references similar research. The calculation result shows that Jatimulyo Urban Communities is included in the moderate sustainability level, where density is moderate (101.1-200 people/ha), has a moderate building density (20-40 buildings/ha), has a random diversity level (1.0) and an entropy index (0.51), and compactness is near perfect inequality (Gini Coefficient 0.99).